FAKTOR-FAKTOR PENYEBAB PERILAKU BULLYING SISWA DI SMK TRIGUNA UTAMA CIPUTAT TANGERANG SELATAN - Suhendar, Risha Desiana (Social Welfare Study Program, 2019)
Abstract. Bullying is the act of using power to hurt someone or a group of people both verbally, physically, and psychologically so that the victim feels depressed and helpless. The act of bullying is not something new among students, bullying is synonymous with the age of teenagers who are still in school. There are many factors that cause student bullying in school. The purpose of this research is to find out the extent of the influence of family, mass media and peers on bullying actions of students at Triguna Utama Ciputat Vocational School in South Tangerang. In this study, researchers used a qualitative approach with a type of descriptive research. While the data collection technique is done through interviews, observation and documentation. The results show that family factors are the cause of bullying behavior of students in schools, families that give less attention and supervision to their children, families are not harmonious, often quarrel, lack of communication with children. then the mass media factor is also the cause of student bullying, students often play online games or watch television which contains elements of violence. And peer factors, because students spend a lot of time in school. In addition, adolescence is a period where children are looking for self-identity, so there is a sense of wanting to be recognized and trying to become a ruler who is feared by other students.Abstrak. Bullying adalah tindakan penggunaan kekuasaan untuk menyakiti seseorang atau sekelompok orang baik secara verbal, fisik, maupun psikologis sehingga korban merasa tertekan dan tak berdaya. Tindakan bullying bukan sesuatu yang baru di kalangan peserta didik, bullying identik dengan usia remaja yang masih sekolah. Ada banyak faktor penyebab tindakan bullying siswa di sekolah. Tujuan penelitian ini untuk mengetahui sejauh mana pengaruh dari faktor keluarga, media massa dan teman sebaya terhadap tindakan bullying siswa di sekolah SMK Triguna Utama Ciputat Tangerang Selatan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Sedangkan teknik pengumpulan datanya dilakukan melalui wawancara, observasi dan dokumentasi. Hasilnya menunjukan bahwa faktor keluarga menjadi penyebab perilaku bullying siswa di sekolah, keluarga yang kurang memberikan perhatian dan pengawasan pada anak-anaknya, keluarga tidak harmonis, sering bertengkar, kurangnya komunikasi dengan anak. Kemudian faktor media massa juga menjadi penyebab tindakan bullying siswa, siswa sering memainkan game online atau menonton televisi yang di dalam nya mengandung unsur kekerasan. Serta faktor teman sebaya, karena siswa banyak menghabiskan waktu di sekolah. Selain itu juga masa remaja merupakan masa di mana anak sedang mencari identitas diri, sehingga ada rasa ingin diakui dan berusaha menjadi penguasa yang ditakuti oleh siswa-siswa lainnya.